Interference management based on clustering in RIS-aided ultra dense network under multicell scenario - Susanto, Misfa; Gumilang, Alisha Gita; Fitriawan, Helmy; Aziz, Azrina Abd (Institute of Advanced Engineering and Science, 2025)
Ultra dense network (UDN) and reconfigurable intelligent surface (RIS) are two latest technologies in encountering the increasing demands for network capacity and quality of service in wireless cellular networks. UDN is created by densely deploying femtocells in macrocells area. It causes complex interferences because distances among femtocells are likely very close. RIS provides solution in regulating the reflection of the signal emitted from the transmitter to the receiver to resolve the obstacles. However, RIS reflects the interference signals as well causing more complex interference problems. This paper proposes a solution using clustering method as interference management in RIS-aided UDN network. By clustering method, nearby femtocells are grouped and allocated different frequency channels among femtocells in a cluster. The performance of two systems–the baseline system and the one employing a clustering method–is evaluated based on signal to interference plus noise ratio (SINR), throughput, and bit error rate (BER). Simulation results indicate that SINR and throughput improved by 1.57% and 1.73%, respectively. Meanwhile, the BER for the baseline system is 5.78×10-8 and decreased when applying the proposed method system with a value of 2.26×10-8. The proposed clustering method is promising to confront the interference problems.